PEMIKIRAN M. QURAISH SHIHAB PADA NILAI-NILAI PENDIDIKAN ISLAM DALAM KONSEP MODERASI BERAGAMA - Suwandi Suwandi; Supriyanto Supriyanto (Zawiyah: Jurnal Pemikiran Islam, 2022)
This study aims to find out about the thoughts of m. Quraish Shihab on the values of Islamic education in the concept of religious moderation. The type of this research is literature study and bibliographic study, with a historical approach of thought related to text studies, covering the genesis of thought, consistency of thought, evolution of thought, systematics of thought, development and change, variants of thought, communication of thought, dialectic of thought and continuity of thought. The research data were taken from several written references, both books and journals, then collaborated so that they became a unified whole in the research results. The results showed that Muhammad Quraish Shihab's ideas about wasathiyah referred to wasathiyah values or moderation, namely based on religious values, and to determine wasatiyah must have religious knowledge. The educational values contained in Muhammad Quraish Shihab's thoughts are the belief in God (Faith), Morals (Submission), Worship, Community Life and Social Relations.